Revisiting the Land Conversion of the Protected Forest for the Mining Industry in Tumpang Pitu, Banyuwangi - Dimas Bagus Triatmojo; Warah Atikah; Nurul Laili Fadhilah (Indonesian Journal of Law and Society, 2020)
Indonesia is a country that has abundant natural resources, both renewable and non-renewable. The wealth of natural resources contained in the motherland can be utilized for the needs and welfare of the people of Indonesia under Article 33 paragraph (3) of the 1945 Constitution. One of the natural resources in Indonesia is forests. The government establishes a forest area as a protected forest area for a benefit that is expected by law. There is a violation of the use of protected forest areas for interests outside the forestry sector, namely the conversion of the function of protected forests used as mining land violations that are contrary to Article 38 Paragraph 4 of Law Number 41 of 1999. Mining business activities have negative impacts as well as positive impacts that arise. Mining will harm environmental conditions that can affect the social life of the community, reducing the environmental quality of the positive impact of the existence of mining business activities in an area will cause changes to the economic level, the legal basis for protecting the affected communities in the mining sector, as mandated by Article 28G Paragraph (1) and Article 28H Paragraph (1) of the 1945 Constitution. Keywords: Transfer of Protection Forest Functions, Mining Impacts.